Sustainable Farming as Counterbalance: Revitalizing Pomponangi Farmer Group in Mining and Industrial Park-Dominated Regions - Chrisma Virginia; Harry Cahyono; Oktsyavitto Adhitya Nugroho; Irwanto Irwanto (Riviera Publishing, 2025)
This study aims to evaluate the effectiveness of the